W-Band Millimeter-Wave Vector Signal Generation Based on Precoding-Assisted Random Photonic Frequency Tripling Scheme Enabled by Phase Modulator - Xinying Li; Yuming Xu; Jiangnan Xiao; Jianjun Yu (IEEE Photonics Journal)
We propose W-band photonic millimeter-wave (mm-wave) vector signal generation employing a precoding-assisted random frequency tripling scheme enabled by a single phase modulator cascaded with a wavelength selective switch (WSS). The selected two optical subcarriers from the phase modulator output by the WSS can have several different kinds of combinations with asymmetrical orders, such as (−3, 0), (−2, 1), (−1, 2), and (0, 3). Employing our proposed precoding-assisted random frequency tripling scheme, we experimentally demonstrate 1/2-Gbd 81-GHz quadrature-phase-shift-keying (QPSK) mm-wave vector signal generation and its wireless delivery over 0.5-m air space distance. We also experimentally demonstrate that the generated mm-wave vector signal based on the minus second-order (−2nd) and first-order (1st) subcarriers, which is equivalent to that based on the minus first-order (−1st) and second-order (2nd) subcarriers, has a better bit-error-ratio (BER) performance than that based on the minus third-order (−3rd) and central (0th) subcarriers, which is equivalent to that based on the 0th and third-order (−3rd) subcarriers, when the phase modulator has a relatively small driving radio-frequency (RF) voltage, whereas an opposite result occurs when the phase modulator has a relatively large driving RF voltage, which is consistent with both our theoretical analysis and numerical simulation.